8-3(-3+7x)=-7

Simple and best practice solution for 8-3(-3+7x)=-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8-3(-3+7x)=-7 equation:



8-3(-3+7x)=-7
We move all terms to the left:
8-3(-3+7x)-(-7)=0
We add all the numbers together, and all the variables
-3(7x-3)+8-(-7)=0
We add all the numbers together, and all the variables
-3(7x-3)+15=0
We multiply parentheses
-21x+9+15=0
We add all the numbers together, and all the variables
-21x+24=0
We move all terms containing x to the left, all other terms to the right
-21x=-24
x=-24/-21
x=1+1/7

See similar equations:

| 4m-16=4(7m-4) | | 4x-1=4x+9 | | 8-3(-3+7x)=-7=3x | | 180=x+x+(3x+25) | | 4(-8x+5)+13=-32-13 | | -117=-3x+4(-x-10) | | m10-m2=8 | | 1/4m-3=9 | | 4a+27=55 | | x=49+5/7 | | 2b=3.32 | | 3+0.90=x | | 4x+(7/6)=5x-(7/6) | | 158g-5=0.53 | | 251(24x-168)=2510(30-6) | | (2x+25)+(3x-7)+(4x-18)+(3x+16)+(2x+8)=720 | | -2x+10-48-36x=4x+4x | | -2+5/6d=11 | | w/3=-1/33 | | (1x-3)/6=-2 | | -8(6+2b)=-6(b-4)-2b | | 10=3x-8x | | 3b-7+4b=6-2b-4 | | i-73=1234 | | 13x-9+2x-4=12x-4+2 | | 6x+5(-x+-20)=107 | | -(4x+8)=-19 | | 1/4w=-11/4 | | x+3/2-x-1/4=x+6/3 | | x(1-x)=2.9 | | 38.72+23.19-x=31.18 | | 2(2x+4)=(3/4)(24-8x) |

Equations solver categories